How does the new developed curriculum affect the perception of medical graduates at King Abdulaziz University about professionalism? - Eldeek, Basem S.; Alghamdi, Naif A.; Alghamdi, Sarah S.; Alghanemi, Logain G.; Almaghthawi, Wael H.; Shawwa, Lana Al; Ayuob, Nasra (International Journal of Research in Medical Sciences, 2017)
Background: In 2007 Faculty of Medicine (FOM), King Abdulaziz University (KAU) reoriented the medical curriculum and integrated professionalism. This study was conducted to assess the perception of professionalism attitudes by medical graduates who graduated from the new curriculum that incorporated the professionalism module and compare it to those who did not. Methods: This cross sectional study was conducted at the teaching hospital of the FOM, KAU using a modified version of the well-constructed questionnairedesigned to assess the student’s attitudes toward professionalism was distributed to all interns in the academic year of 2013-2014. Statistical analysis was carried out using Statistical Package of Social Science (SPSS) version 16. Results: Higher mean scores with significant differences in all aspects of professionalism were observed in interns graduated from the new curriculum when compared to those of the old one and was previously reported by Eldeek et al., (2012). The importance of adhering to high ethical and moral behavior and the need of humanity in the efficacy of the medical practice were the most significant attributes with effect size of 0.64 and 0.58 respectively. Studying in the clinical years represented the first helpful source of the participant to develop their perception about professionalism. Conclusion: The new developed curriculum at the FOM succeeded to improve the graduate perception about professionalism.